2008
DOI: 10.1380/ejssnt.2008.152
|View full text |Cite
|
Sign up to set email alerts
|

Field Emission from W Tips Sharpened by Field-Assisted Nitrogen and Oxygen Etching

Abstract: Field emission properties were studied for tips sharpened using field-assisted nitrogen and oxygen etching. Sharp single crystal tungsten <111>-oriented tips were fabricated and evaluated by Fowler-Nordheim plots and field-ion microscopy observations. The results demonstrated emissions at lower bias voltages due to the sharpening of the tip apex using the etching. The field emission properties and tip shapes after nitrogen etching were compared with those obtained after oxygen etching.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
8
0

Year Published

2009
2009
2021
2021

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 11 publications
(8 citation statements)
references
References 17 publications
0
8
0
Order By: Relevance
“…In the field-assisted nitrogen etching process, a specific nanoprotrusion was formed on the tip-apex to obtain a higher angular current density. We performed a modified method based on a field-assisted nitrogen etching, which was reported by Rezeq et al and Onoda et al in detail [5,6]. The nanoprotrusion with a hemispherical shape even along ⟨111⟩ direction could be formed on the tip-apex with a significantly large radius of curvature by the modified field-assisted nitrogen etching process.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…In the field-assisted nitrogen etching process, a specific nanoprotrusion was formed on the tip-apex to obtain a higher angular current density. We performed a modified method based on a field-assisted nitrogen etching, which was reported by Rezeq et al and Onoda et al in detail [5,6]. The nanoprotrusion with a hemispherical shape even along ⟨111⟩ direction could be formed on the tip-apex with a significantly large radius of curvature by the modified field-assisted nitrogen etching process.…”
Section: Methodsmentioning
confidence: 99%
“…In order to more improve the angular current density of GFIS we have developed tungsten emitter-tips with a specific nanoprotrusion on the tip-apex by using a modified field-assisted oxygen etching, followed by a field evaporation process to fabricate a trimer on the nanoprotrusion [4]. Whereas, nitrogen etching process, in which a subnanometric protrusion such as a single tungsten atom could be formed on ⟨110⟩-or ⟨111⟩-oriented crystalline tungsten emitter-tips [5,6].…”
Section: Introductionmentioning
confidence: 99%
“…It was described that if the taper angle of emitter-shank becomes smaller, then a larger ion current could be obtained. Onoda et al reported field-assisted oxygen etching as a fabrication method for field electron emitter tips terminated by a single-atom [6][7][8]. In this study, to focus more effectively an ion beam, we modified the field-induced oxygen etching method to optimize the shape of field ion emitter tip with a nanoprotrusion.…”
Section: Introductionmentioning
confidence: 99%
“…Recently, to obtain an emitter tip with a better emission property, a method of preparing an emitter tip having a nanoprotrusion terminated by a single atom or a trimer has been actively investigated. 2,3 For this situation, the helium ion microscope as a powerful apparatus for surface analysis was developed by ALIS corporation in 2006 by using a trimer-terminated W ͑111͒ emitter tip. 4 However, the shape of the emitter shank still remains as a subject of investigation for obtaining an ion beam with a higher dI / d⍀.…”
Section: Introductionmentioning
confidence: 99%